2004
DOI: 10.17221/4054-pse
|View full text |Cite
|
Sign up to set email alerts
|

The spatial variability of mineral nitrogen content in topsoil and subsoil

Abstract: Spatial variability of soil mineral nitrogen N min + , N-NO 3 -) in a soil profile down to 60 cm was determined in a 19-ha experimental field in Prague-Ruzyně for four years. Winter wheat was grown in the years 2000 and 2001, oats in 2002 and mustard in 2003. Root length distribution and depth of the crops were determined at four locations representing different soil conditions within the experimental field. The coefficient of variation as the measure of the variability of nitrate N in topsoil and subsoil (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Similar small-scale variation of NO 3 À in grazed pastures has been identified in previous studies, with semi-variograms exhibiting the range of spatial dependency of less than 5 m (White et al, 1987;Broeke et al, 1996;Wade et al, 1996;Bogaert et al, 2000), and a nugget variance of 60% (Bogaert et al, 2000). These results contrast with similar studies performed on arable soils, which were characterised by ranges of spatial dependencies for NO 3 À of greater than 39 m (van Meirvenne et al, 2003;Haberle et al, 2004). The observed variation at larger spatial-scales, especially NO 3 À , could be due to the habit of sheep to frequent certain areas of the pasture such as paths, a drinking trough and areas of shade (Bogaert et al, 2000).…”
Section: Spatial Variation Of Soluble N At Within-field Scalessupporting
confidence: 82%
“…Similar small-scale variation of NO 3 À in grazed pastures has been identified in previous studies, with semi-variograms exhibiting the range of spatial dependency of less than 5 m (White et al, 1987;Broeke et al, 1996;Wade et al, 1996;Bogaert et al, 2000), and a nugget variance of 60% (Bogaert et al, 2000). These results contrast with similar studies performed on arable soils, which were characterised by ranges of spatial dependencies for NO 3 À of greater than 39 m (van Meirvenne et al, 2003;Haberle et al, 2004). The observed variation at larger spatial-scales, especially NO 3 À , could be due to the habit of sheep to frequent certain areas of the pasture such as paths, a drinking trough and areas of shade (Bogaert et al, 2000).…”
Section: Spatial Variation Of Soluble N At Within-field Scalessupporting
confidence: 82%
“…Further, physical soil characteristics and actual moisture before winter vary, due to local weather conditions, the preceding crop, soil management, etc. (Vaněk et al 2003); yet another factor being the variability of spatial N min within a sampled field (Illsemann et al 2001;Haberle et al 2004).…”
Section: The Factors Affecting Calculated Leachingmentioning
confidence: 99%
“…Accordingly, Kohl and Harrach [53] found that the spatial variation in nitrate concentration was always considerably higher in the subsoil (60 cm) of the NT plots than of the CT plots, which shows the effects of macropore flow. Haberle et al [56] found coefficient of variation as the measure of the variability of nitrate N in topsoil and subsoil (0-30 and 30-60 cm) ranged between 18%-39% and 20%-37%, respectively. It was mostly the same or slightly greater in subsoil than in topsoil in respective years.…”
Section: Small-scale Variability Of Soil N Min As Affected By Tillage Intensitymentioning
confidence: 99%